Genetic analysis of the stem rust resistance genes in synthetic hexaploid wheat (Triticum aestivum) lines - MEENA, M R; SINGH, NIRUPMA; JAIN, NEELU; KUMAR, RAVINDER; SINGH, S S (The Indian Journal of Agricultural Sciences, 2015)
The objective of this investigation was to examine the inheritance of stem rust (Puccinia graminis f. sp. tritici) resistance genes in synthetic hexaploid wheat lines and to identify the allelic relationship among the resistant lines. Genetic basis of stem resistance was studied in Synthetic 4, Synthetic 55, and Synthetic 86 and F2:3 population, derived from (susceptible cultivar, i.e. Agra local × resistant lines (Synthetic 4, Synthetic 55, and Synthetic 86). Isolate 40A of Puccinia graminis tritici (most prominent stem rust pathotype in India) was used to examine the segregation pattern. The results revealed that resistance in Synthetic 4 and Synthetic 55 for pathotype 40A was governed by a single dominant gene, as F2 seedlings segregates in a ratio of 3:1. While, resistance in Synthetic 86 was governed by two genes, i.e. one dominant and one recessive gene, as F2 seedling depicted 13:3 segregation ratio, which further conferred by F3 family data. Allelism studies (using as F2 population derived from a cross between Synthetic 4 × Synthetic 55), revealed the resistant gene present in these line was same. However, F2 population derived from Synthetic 4 × Synthetic 86 and Synthetic 55 × Synthetic 86 showed that the resistant gene in Synthetic 86 was different from Synthetic 4 and Synthetic 55 as seedling of F2 population segregated in ratio of 61:3.